Isolation and transplantation of sturgeon early-stage germ cells - Pšenička, Martin; Saito, Taiju; Linhartová, Zuzana; Gazo, Ievgeniia (Theriogenology, 2015)
We report, for the first time, a series of baseline techniques comprising isolation and transplantation of female and male early-stage germ cells in sturgeon to generate a germline chimera as a potential tool for surrogate reproduction and gene banking. Cells were dissociated from testis, characterized by mostly spermatogonia, and from ovary, exclusively comprising oogonia and previtellogenic oocytes, of Acipenser baerii, using 0.3% trypsin (2 hours, 23 °C) dissolved in PBS, isotonic with blood plasma. The dissociated germ cells were sorted by Percoll gradient centrifugation followed by immunolabeling with germ cell-specific vasa antibody DDX4, while 10% to 30% Percoll solution contained 79.4% and 70.8% labeled testicular and ovarian cells. Sorted germ cells were transplanted into a cavity close to a presumptive genital ridge of newly hatched heterospecific Acipenser ruthenus larvae with fluorescein isothiocyanate-labeled endogenous primordial germ cells. The transplanted germ cells were randomly distributed in the body cavity through 30-day posttransplantation (dpt). Subsequently, the cells were organized into genital ridges 50 dpt and proliferated 90 dpt. The number of both transplanted and endogenous germ cells significantly increased from 18.1, 22.2, and 29.1 (30 dpt) to 108.5, 90.8, and 118.5 (90 dpt) in ovarian, testicular, and endogenous germ cells, respectively (P < 0.05). The efficiency of transplantation was 60% (counted 90 dpt).
Keywords: Germline chimera; Germ Cells; Sturgeon; Vas; pohlavní dospělost; mužské pohlaví; testis; Spermatogonium; Oogonium; ženské pohlaví; zvířata; ovarium; zárodečné buňky; Ovary; Germ cell; Fishes; Sexual Maturation; ryby; Female; Testis; Male; Animals